2014
DOI: 10.2478/s13382-014-0316-2
|View full text |Cite
|
Sign up to set email alerts
|

Neurological and neurophysiological examinations of workers exposed to arsenic levels exceeding hygiene standards

Abstract: Objectives: The assessment of the neurotoxic effect of arsenic (As) and its inorganic compounds is still the subject of interest due to a growing As application in a large array of technologies and the need to constantly verify the principles of prevention and technological parameters. The aim of this study was to determine the status of the nervous system (NS) in workers exposed to As at concentrations exceeding hygiene standards (Threshold Limit Values (TLV) -10 μg/m 3 , Biological Exposure Index (BEI) -35 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…However, in recent decades it was shown that this element might be toxic to plants, animals, and humans. [10][11][12][13] Usually, human Al exposure is primarily through the diet, the typical adult's dietary intake being around 3 to 12 mg Al/d. 14 Al lactate is often used as representative Al soluble salts, with enhanced gastrointestinal absorption.…”
mentioning
confidence: 99%
“…However, in recent decades it was shown that this element might be toxic to plants, animals, and humans. [10][11][12][13] Usually, human Al exposure is primarily through the diet, the typical adult's dietary intake being around 3 to 12 mg Al/d. 14 Al lactate is often used as representative Al soluble salts, with enhanced gastrointestinal absorption.…”
mentioning
confidence: 99%
“…Acute arsenic intoxication is strongly related to symmetrical peripheral neuropathy in the upper and lower limbs, so that the causal relation here is clear (Rodríguez, Jiménez‐Capdeville, & Giordano, ; Vahidnia, van der Voet, & de Wolff, ). In addition, phrenic neuropathy with unilateral elevation of the diaphragm (Bansal, Haldar, Dhand, & Chopra, ) and fatigue (Bajorin, Halabi, & Small, ; Sińczuk‐Walczak et al, ) have been associated with arsenic.…”
Section: Discussionmentioning
confidence: 99%
“…Neurobehavioral changes have been reported in exposed welders (157)(158)(159)(160)(161)(162)(163). Neurobehavioral changes have been reported in exposed welders (157)(158)(159)(160)(161)(162)(163).…”
Section: Neurological Effectsmentioning
confidence: 98%